Sosialisasi Penerapan Akuntansi Dasar dan Pemasaran Digital di Desa Cileles, Jatinangor - Ignatius Oki Dewa Brata; Bunga Indah Bayunitri; Erly Sherlita; Eriana Kartadjumena; H. R. Roosaleh Laksono Tri Yuliawan (FKIP, Universitas Palangka Raya, 2026)
This community service activity was conducted in Cileles Village and targeted catfish farming groups. The activity was motivated by the low level of basic accounting literacy and the limited use of digital marketing in managing catfish farming businesses, which hindered business development and market expansion. The objective of this community service program was to improve the community’s capacity in financial management through the application of basic accounting and the introduction of digital marketing as a promotional medium for catfish products. The program applied a participatory approach consisting of socialization, training in basic accounting and digital marketing, practical exercises and simulations, as well as mentoring and evaluation activities. The results demonstrated an improvement in participants’ understanding of financial record keeping, production cost calculation, and the preparation of simple profit and loss reports. In addition, participants began utilizing digital media as a marketing strategy to expand product promotion and reach broader markets. This activity positively contributed to strengthening managerial and marketing capacities among catfish farming business actors and supported the sustainability and development of community-based businesses in rural areas.